Respuesta :

~ Simplifying

-4x + -4 = -7(x + 4)

~ Reorder the terms:

-4 + -4x = -7(x + 4)

~ Reorder the terms:

-4 + -4x = -7(4 + x)

-4 + -4x = (4 * -7 + x * -7)

-4 + -4x = (-28 + -7x)

~ Solving

-4 + -4x = -28 + -7x

~ Solving for variable 'x'.

~ Move all terms containing x to the left, all other terms to the right.

~ Add '7x' to each side of the equation.

-4 + -4x + 7x = -28 + -7x + 7x

~ Combine like terms: -4x + 7x = 3x

-4 + 3x = -28 + -7x + 7x

~ Combine like terms: -7x + 7x = 0

-4 + 3x = -28 + 0

-4 + 3x = -28

~ Add '4' to each side of the equation.

-4 + 4 + 3x = -28 + 4

~ Combine like terms: -4 + 4 = 0

0 + 3x = -28 + 4

3x = -28 + 4

~ Combine like terms: -28 + 4 = -24

3x = -24

~ Divide each side by '3'.

x = -8

~ Simplifying

x = -8

One solution (x=-8)

Work is posted below

Hope this helps comment below for more questions :)
Ver imagen lauren6751
ACCESS MORE